The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fphys.2017.00999
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells from Dental Pulp: What Epigenetics Can Do with Your Tooth

Abstract: Adult stem cells have attracted scientific attention because they are able to self-renew and differentiate into several specialized cell types. In this context, human dental tissue-derived mesenchymal stem cells (hDT-MSCs) have emerged as a possible solution for repairing or regenerating damaged tissues. These cells can be isolated from primary teeth that are naturally replaced, third molars, or other dental tissues and exhibit self-renewal, a high proliferative rate and a great multilineage potential. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 157 publications
(201 reference statements)
0
58
0
1
Order By: Relevance
“…In this study, two cell types, GFs and DPMCs, originating from different anatomical sites and having distinctive roles in regeneration and healing of damaged periodontal (Sisman, Aksoy, Yalcin, & Karaoz, 2016;Smith, Caceres, Martinez, Oyarzun, & Martinez, 2015) and dental pulp tissues (Patil et al, 2014;Rodas-Junco, Canul-Chan, Rojas-Herrera, De-la-Pena, & Nic-Can, 2017;Sonoyama et al, 2008) were assessed for their potential to regenerate gingival connective tissues (lamina propria) (Chiquet et al, 2015) and dental pulp (Huang, Gronthos, & Shi, 2009) in vitro. Such assessment is seen as necessary in predicting a success of restoration of deciduous teeth or traumatized tissues and the formation of tertiary dentin as a protective barrier for dental pulp.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two cell types, GFs and DPMCs, originating from different anatomical sites and having distinctive roles in regeneration and healing of damaged periodontal (Sisman, Aksoy, Yalcin, & Karaoz, 2016;Smith, Caceres, Martinez, Oyarzun, & Martinez, 2015) and dental pulp tissues (Patil et al, 2014;Rodas-Junco, Canul-Chan, Rojas-Herrera, De-la-Pena, & Nic-Can, 2017;Sonoyama et al, 2008) were assessed for their potential to regenerate gingival connective tissues (lamina propria) (Chiquet et al, 2015) and dental pulp (Huang, Gronthos, & Shi, 2009) in vitro. Such assessment is seen as necessary in predicting a success of restoration of deciduous teeth or traumatized tissues and the formation of tertiary dentin as a protective barrier for dental pulp.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs的细胞分化和转分化领域 [174] . MSCs细胞内 DNA和组蛋白上发生的可逆化学修饰, 能改变MSCs 的分化潜能, 并决定细胞最终的分化命运 [175] . Saidi等 人 [176] [186] .…”
Section: Mscs表观遗传学调控相关的研究大部分集中在unclassified
“…The identification molecular mechanisms involved in lineage specification could contribute to better understanding of TDSCs behavior. Increasing evidence indicated that a variety of cellular and molecular mechanisms could affect the stem cells fate (Rodas‐Junco et al, ). These mechanisms control stem cells fate behaviors during development.…”
Section: Molecular Mechanisms In the Regulation Of Cellular Differentmentioning
confidence: 99%
“…MiRNAs are other factors that could be involved in dental stem cells fate (Rodas‐Junco et al, ). miRNAs are small noncoding RNAs that act as epigenetic regulators (Gholamin et al, ; Golabchi et al, ; Keshavarzi et al, ; Mirzaei et al, ; Mirzaei et al, ).…”
Section: Molecular Mechanisms In the Regulation Of Cellular Differentmentioning
confidence: 99%